Comparing handgrip strength between judokas and non-judokas using population-based normative values - Külkamp, W.; Kons, R. L.; de Souza, J.; Hizume-Kunzler, D.; Ache-Dias, J.; Carvalho, R.; Pupo, J. D.; Detanico, D. (Sport Sciences for Health, 2024)
Purpose Recently, a novel index (HGSindex) was proposed to compare the handgrip strength (HGS) within and between judokas and non-judokas considering the body mass (BM). However, some studies consider body height (BH) as the most appropriate parameter. So, the aims of the present study were as follows: (1) determine which variable (BM or BH) provides a better normalization of the HGS in groups of judokas and non-judokas and (2) evaluate the HGS of these groups using the HGSindex based on normative values.